Herbal Products and Their Active Constituents Used Alone and in Combination with Antibiotics against Multidrug-Resistant Bacteria - Herman, Anna; Herman, Andrzej P. (Planta Medica, 2022)
The purpose of this review is to summarize the current knowledge acquired on herbal products and their active constituents with antimicrobial activity used alone and in combination with antibiotics against multidrug-resistant bacteria. The most promising herbal products and active constituents used alone against multidrug-resistant bacteria are Piper betle (methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus, extended-spectrum beta-lactamase, Acinetobacter baumannii, Pseudomonas aeruginosa), Glycyrrhiza glabra (methicillin-resistant S. aureus, vancomycin-resistant Enterococcus, P. aeruginosa), and berberine (methicillin-resistant S. aureus, A. baumannii, P. aeruginosa), respectively. The synergistic effect of the combination of herbal products and their active constituents with antibiotics against multidrug-resistant bacteria are also described. These natural antibacterial agents can be promising sources of inhibitors, which can modulate antibiotic activity against multidrug-resistant bacteria, especially as efflux pump inhibitors. Other possible mechanisms of action of herbal therapy against multidrug-resistant bacteria including modification of the bacterial cell wall and/or membrane, inhibition of the cell division protein filamenting temperature sensitive Z-ring, and inhibition of protein synthesis and gene expression, all of which will also be discussed. Our review suggests that combination herbal therapy and antibiotics can be effectively used to expand the spectrum of their antimicrobial action. Therefore, combination therapy against multidrug-resistant bacteria may enable new choices for the treatment of infectious diseases and represents a potential area for future research.
Keywords: herbal products; active constituents; multidrug-resistant bacteria; antibiotics; synergistic therapy